Kondisi Fisik dan Teknik Atlet Pencak Silat Pagar Nusa Kabupaten Temanggung (Universitas Negeri Semarang, 2022)
Adi Setyawan. 2022. Physical and Technical Condition of Pagar Nusa Pencak Silat Athletes in Temanggung Regency. Thesis on Health & Recreation Physical Education / Health and Recreation Physical Education Study Program. Faculty of Sport Science. Semarang State University. Advisor Dr. Ipang Setiawan, S. Pd., M. Pd. Keywords: Pencak Silat, Physical Condition, Technique The background of this research is the Physical and Technical Condition of the Pagar Nusa Pencak Silat athletes in Temanggung Regency. pencak silat athletes who have good physical and technical skills will have a great chance of achievement. The problem in the research is how the physical conditions of strength, agility, speed, endurance, flexibility, accuracy, and agility are. Physical condition and technique are an interconnected entity because physical condition is the basis for maintaining stamina so that athletes stay focused when performing basic pencak silat techniques. The purpose of this study was to determine the physical conditions which include strength, agility, speed, endurance, flexibility, accuracy, and agility and the technical conditions of respect, stance, step patterns, punches, kicks, catch pad athletes, especially the Pagar pencak silat branch. Nusa in Temanggung Regency. This research uses quantitative research and uses descriptive percentage method with survey technique. With survey techniques and standardized tests with a population of 54 athletes. The samples used were 25 male athletes and 23 female athletes. The sampling technique used is purposive sampling. Researchers in this case are trying to describe or provide an overview of the state of the physical condition and technique of the Pagar Nusa pencak silat athlete, Temanggung Regency. The results of this study were the physical condition of the male pencak silat athletes from Pagar Nusa, Temanggung Regency, which had an average score of 3.25 in the medium category. The physical condition of the female pencak silat athlete in Pagar Nusa, Temanggung Regency, has an average score of 2.9 in the less category. The basic technical skills of the male pencak silat athletes, members of Pagar Nusa Pringsurat, Temanggung Regency have an overall average of 83.50% in the good category. The basic technical skills of female pencak silat athletes who are members of Pagar Nusa, Temanggung Regency have an overall average of 76.56% in the medium category. The conclusion of the study is that the physical ability of the male pencak silat athletes of Pagar Nusa in Temanggung Regency is in the moderate category. The physical ability of female pencak silat athletes from Pagar Nusa in Temanggung Regency is in the poor category. The technical ability of the male pencak silat athletes of Pagar Nusa in Temanggung Regency is in the good category. The technical ability of the female pencak silat athlete of Pagar Nusa in Temanggung Regency is in the medium category.